The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsphotonics.1c00297
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Spectroscopy of Plasmonic Titanium Nitride Nanoparticle Lattices

Abstract: Titanium nitride (TiN) is an advantageous plasmonic material for optoelectronic applications that require resilience to extreme irradiation or temperatures. Although TiN is optically similar to noble metals at near-infrared wavelengths under steadystate excitation conditions, their photoexcited properties are distinct at ultrafast time scales. This paper describes the differences in optical properties between coupled TiN nanoparticles in 2D arrays that support surface lattice resonances (SLRs) and TiN nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…), SiC, and TiN with wide bandgaps exhibit prominent optical properties for alternative plasmonic materials in NIR and visible spectral ranges. [ 223 ] TiN NP arrays have been demonstrated to remain intact at pump power 2–3 orders of magnitude higher than the saturation fluence of Au NPs (Figure 13c). Both dipolar SLR and quadrupolar SLR can be supported in TiN NP arrays in the NIR range (Figure 13d).…”
Section: Plasmonic Materials Beyond Noble Metalsmentioning
confidence: 99%
“…), SiC, and TiN with wide bandgaps exhibit prominent optical properties for alternative plasmonic materials in NIR and visible spectral ranges. [ 223 ] TiN NP arrays have been demonstrated to remain intact at pump power 2–3 orders of magnitude higher than the saturation fluence of Au NPs (Figure 13c). Both dipolar SLR and quadrupolar SLR can be supported in TiN NP arrays in the NIR range (Figure 13d).…”
Section: Plasmonic Materials Beyond Noble Metalsmentioning
confidence: 99%
“…This has provided a rich library for the design of various antenna/semiconductor heterointerfaces, which imparts an additional degree of freedom for the regulation of the dynamic process of photocarriers that is critical to hot carrier extraction. Thus far, a number of competitive non-noble plasmonic competitors have emerged including Al, [84] Cu, [85] Si, [86] Ge, [87] TiN, [88] Cu x S, [89] Cu 2-x Se, [90] MoO 3-x , [91] WO 3-x , [92] MXene, [93] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic nanostructures belong to an emerging class of materials whose optical properties take advantage of localized and delocalized surface plasmon (SP) resonance, which gives rise to large enhancement of the electromagnetic field, subwavelength confinement, and thermal effects. They have numerous applications, such as in optical sensors, nonlinear optical devices, biosensors, and bactericidal materials. SPs were previously considered to arise from metallic structures and to be controlled by the shapes, sizes, and dielectric environments of such materials. Ongoing research has demonstrated that SPs in highly doped semiconductors, perovskites, transparent metal oxides, and metal nitrides/dichlorchalcogenides are of the same status as those seen with metallic structures. …”
Section: Introductionmentioning
confidence: 99%